Analisis Durasi Pemeraman terhadap Kadar dan Jumlah Bioetanol yang dihasilkan dari Limbah Buah Pasar - Isdianto isdi; Murdani (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2023)
ABSTRACT The need for fuel derived from natural resource raw materials in Indonesia is increasing from year to year. Fruit and vegetable waste is very disturbing the environment, so research to utilize fruit waste such as banana and pineapple waste for conversion as alternative energy source like bioethanol is very important. This research was conducted to determine the effect of fermentation time on the volume and alcohol content of market fruit waste. The method uses a descriptive quantitative analytical method by measuring the volume and alcohol content produced from various fermentation times. There are three treatments based on differences in fermentation time, (1) three days, (2) five days, and (3) seven days. Measurements were made on the volume and content of bioethanol produced after the distillation process. Data analysis carried out in this study used a descriptive regression method by analyzing differences in volume and bioethanol content from each treatment. The results of the research show that the longer the fermentation is carried out, the more it will affect the volume and level of bioethanol produced. The best fermentation time is 168 hours or 7 days, because in this condition it shows optimal results obtaining a bioethanol content of 84%.